The Date of the Conversion of the Visigoths - Thompson, E. A. (The journal of ecclesiastical history, 1956)
When the Visigoths crossed the Danube in 376 and entered the Roman provinces, were they Christian or pagan? Were the two armies which clashed at Adrianople on 9 August 378 composed substantially of Christians, or were the victors still pagan? When Ulfila, the Apostle of the Goths, died c. 382, had he succeeded in converting his fellow countrymen to Christianity? It will be argued here that it would be inconsistent with such evidence as exists to suppose that the Visigoths were a Christian people at any of these dates